2(t-9)+-18=-4

Simple and best practice solution for 2(t-9)+-18=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(t-9)+-18=-4 equation:


Simplifying
2(t + -9) + -18 = -4

Reorder the terms:
2(-9 + t) + -18 = -4
(-9 * 2 + t * 2) + -18 = -4
(-18 + 2t) + -18 = -4

Reorder the terms:
-18 + -18 + 2t = -4

Combine like terms: -18 + -18 = -36
-36 + 2t = -4

Solving
-36 + 2t = -4

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 2t = -4 + 36

Combine like terms: -36 + 36 = 0
0 + 2t = -4 + 36
2t = -4 + 36

Combine like terms: -4 + 36 = 32
2t = 32

Divide each side by '2'.
t = 16

Simplifying
t = 16

See similar equations:

| -12+1.5y-6y=18 | | m+3-5=-5m+3m+7 | | 8x-4=8x-20 | | 4r+48/16=2r-18/2 | | 5/244/24 | | 18(n)=7.2 | | 24.50t+9.50=c | | 3-6(2v+3)=-111 | | 5.27=0.02036x(1-0.02036) | | 4x-36-24x=2-(6+4x) | | 4(x+3)+44=-4x | | -9+(5x)=6x-4 | | -3x-6-9x=7 | | -8+x+x=10 | | 7(2-5y)+10y=89 | | Ax-9=12 | | 5.27=0.0509x(1-0.0509) | | -9(5x)=6x-4 | | 2x-5(x-2)=-8+3x-6 | | 12x-30=4x+2 | | 15x^2+x-7/3x+2 | | x/2-1.25=5 | | x-4/4-1=x-10/5 | | 5x+26=21+4x | | 11x+4=4x+25 | | 7m+2(15/4m-3/2) | | 2(x+4)/3=4x-5 | | 4d+3=5d+2 | | (x-3)(x+8)(x)(x-5)=360 | | x-2/5-1=x-11/6 | | u^2-28u+24=0 | | 5(2+3(x+1))= |

Equations solver categories